Relationship between high‐risk alcohol consumption and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) seroconversion: a prospective sero‐epidemiological cohort study among American college students. (22nd February 2022) - Kianersi, Sina; Ludema, Christina; Macy, Jonathan T.; Chen, Chen; Rosenberg, Molly
Abstract: Aims: To estimate the associations between high‐risk alcohol consumption and (1) severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) seroconversion, (2) self‐reported new SARS‐CoV‐2 infection and (3) symptomatic COVID‐19. Design: Prospective cohort study. Setting: Indiana University Bloomington (IUB), IN, USA. Participants: A total of 1027 IUB undergraduate students (64% female), aged 18 years or older, residing in Monroe County, Indiana, seronegative for SARS‐CoV‐2 at study baseline. Measurements: Primary exposure was high‐risk alcohol consumption measured with an Alcohol Use Disorders Identification Test (AUDIT) questionnaire score of 8 or more. Primary outcome was SARS‐CoV‐2 seroconversion since baseline, assessed with two SARS‐CoV‐2 antibody tests, at baseline (September 2020) and end‐line (November 2020). Secondary outcomes were (a) self‐reported new SARS‐CoV‐2 infection at the study end‐line and (b) self‐reported symptomatic COVID‐19 at baseline. Findings: Prevalence of high‐risk alcohol consumption was 32 %. In models adjusted for demographics, students with high‐risk alcohol consumption status had 2.44 [95% confidence interval (CI) = 1.35, 4.25] times the risk of SARS‐CoV‐2 seroconversion and 1.84 (95% CI = 1.04, 3.28) times the risk of self‐reporting a positive SARS‐CoV‐2 infection, compared with students with no such risk. We did not identify any association between high‐risk alcohol consumption and symptomatic COVID‐19 (prevalence ratio = 1.17, 95% CI = 0.93, 1.47). Findings from sensitivity analyses corroborated these results and suggested potential for a dose–response relationship. Conclusions: Among American college students, high‐risk alcohol consumption appears to be associated with higher risk for severe acute respiratory syndrome coronavirus 2 seroconversion/infection.